Current randomized control trials, observational studies and meta analysis in off-pump coronary surgery. Issue 1 (December 2015) - Parissis, Haralabos; Lau, Man; Parissis, Mondrian; Lampridis, Savvas; Graham, Victoria; Al-Saudi, Reza; Mhandu, Peter
Abstract The off-pump literature is divided into three eras: the "early phase" with results favouring off-pump surgery supported with randomized control trials (RCTs) mainly from Bristol, UK; an "intermediate phase" dominated by the results of the ROOBY trial and finally a more "contemporary phase" whereby the off/on-pump argument is unsettled. Although the literature has failed to project an overall superiority of off-pump versus on-pump surgery, nevertheless, small randomized control trials and large meta-analysis studies are concluding that the incidence of a stroke is less than 1 % when an aortic off-pump techniques (especially the non-touch technique) are advocated in patients with diseased ascending aorta. Furthermore, off-pump combined with hybrid procedures may lead to a reduction of adverse outcome in the aged high-risk population with concomitant poor left ventricular function and co-morbidities. The current review attempts to bring an insight onto the last ten years knowledge on the on/off-pump debate, with an aim to draw some clear conclusions in order to allow practitioners to reflect on the subject.